2022
DOI: 10.3389/fenvs.2022.808943
|View full text |Cite
|
Sign up to set email alerts
|

Not Just Another Assessment Method: Reimagining Environmental Flows Assessments in the Face of Uncertainty

Abstract: The numerous environmental flows assessment methods that exist typically assume a stationary climate. Adaptive management is commonly put forward as the preferred approach for managing uncertainty and change in environmental flows. However, we contend that a simple adaptive management loop falls short of meeting the challenges posed by climate change. Rather, a fundamental rethink is required to ensure both the structure of environmental flows assessments, along with each individual technical element, actively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…1 ) used to evaluate the participatory process (shown in yellow). Further detail regarding the participatory process and case study can be found in Horne et al ( 2020 , 2022 ) and in online supplementary materials.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ) used to evaluate the participatory process (shown in yellow). Further detail regarding the participatory process and case study can be found in Horne et al ( 2020 , 2022 ) and in online supplementary materials.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we outline a process for evaluating the success of a participatory approach implemented during an e-flows assessment in Victoria, Australia. The e-flows assessment blended elements of structured decision-making and participatory modeling (Horne et al 2022 , Mussehl et al 2022 ). Our purpose in this paper is not to present the participatory methodology itself, but to focus on the evaluation and assessment of participation.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive management is one method to acknowledge this uncertainty and improve knowledge through testing hypotheses, implementing and monitoring actions, and adjusting future decisions and actions based on the results. Adaptive management is well acknowledged and included in environmental water management (Tonkin et al, 2020;Watts et al, 2020;Horne et al, 2022), but there can be lagged ecological feedbacks, and thresholds or tipping points may pass before managers are even aware. Other reasons also prohibit widespread adoption of adaptive management such as institutional risk aversion of looking like a 'failure' and insufficient resourcing, amongst others (Allan et al, 2008;Stults and Larsen, 2020).…”
Section: Actionmentioning
confidence: 99%
“…There is clear evidence that anthropogenic climate change is occurring, yet agreement on how to adapt environmental flow management is far from absolute. Environmental flow assessments (and recommendations) typically aim to restore ecosystems to an historic condition or protect them from further change and use historic flow regimes to make recommendations (Capon et al, 2018;Horne et al, 2022). However the past is not a good representation of the future and climate adaptation is required when determining flow objectives and recommendations for future environmental water (Judd et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…presented inJudd et al (2022) andHorne et al (2022) Judd et al (2022). suggest a process for setting "climate ready" ecological objectives that incorporate the latest science and community values and iteratively testing objectives against future scenarios until an acceptable trade off (if required) is reached Horne et al (2022). provide a new flow assessment method that uses ecological models to include consideration of future change and uncertainty.…”
mentioning
confidence: 99%